Operations management : an Asian perspective - Stevenson, William J.; Chuong, Sum Chee (Singapore, 2010)
This book is an introduction to operations manage ment. The topics covered include both strategic issues and practical applications. Among the topics are fore casting, product and service design, capacity planning, management of quality and quality control, inventory planning, scheduling, supply chain management, and project management. Operations management is evolving and growing. Previous editions of this book have focused on updating and integrating important information gleaned from the plethora of new developments and perspectives in the field. This edition continues to do that; it incorporates discussion on contemporary issues such as quality, strat egy, inventory, capacity, and project management as well as new material to highlight the growing importance of eco-friendly and green operations and corporate social responsibility.
Keywords: Production management